Indication Cadmium in leaf Eucalyptus camaldulensis plant at Samarra city/Iraq (Texas Journal of Agriculture and Biological Sciences, 2023)
The concentrations and main sources of Cd elements were determined seasonally in leaf plant species Eucalyptus camaldulensis and soil surrounding it at three stations near the Tigris River Samarra city/Iraq during the period from January 2022 to July 2022 . The results showed that the highest mean concentration of Cd in leaf at was (3.013 ng/g dry weight ) in E. camaldulensis and it was (4.906 ng/g in soil . Seasonal variation of Cd concentration showed that the highest mean concentrations were recorded in Spring (3.004 ng/g dry weight) at E. camaldulensis ,while the lowest mean concentrations were recorded in January (1.99 ng/g dry weight) in soil . According to Cd indices evaluating the potential ecological risks resulting from soil and plant pollution with cadmium and determining pollution levels was using enrichment, pollution and geochemical accumulation factors to determine ecological risks using the factors of potential and unilateral environmental risk factor.